2009
DOI: 10.1175/2008mwr2650.1
|View full text |Cite
|
Sign up to set email alerts
|

Bow Echo Mesovortices. Part II: Their Genesis

Abstract: This two-part study examines the damaging potential and genesis of low-level, meso-g-scale mesovortices formed within bow echoes. This was accomplished by analyzing quasi-idealized simulations of the 10 June 2003 Saint Louis bow echo event observed during the Bow Echo and Mesoscale Convective Vortex Experiment (BAMEX). In Part II of this study, mesovortex genesis was investigated for vortices formed at different stages of convective system evolution. During the early ''cellular'' stage, cyclonic mesovortices w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 34 publications
7
38
1
Order By: Relevance
“…17h). The development of only a cyclonically rotating vortex resembles those documented by Atkins and St. Laurent (2009) as observed during the BAMEX experiment.…”
Section: B Sensitivity Testssupporting
confidence: 73%
“…17h). The development of only a cyclonically rotating vortex resembles those documented by Atkins and St. Laurent (2009) as observed during the BAMEX experiment.…”
Section: B Sensitivity Testssupporting
confidence: 73%
“…Atkins and St. Laurent (2009) suggest slightly different mesovortex genesis mechanisms. In quasi-idealized simulations of a bow echo on 10 June 2003 (see Atkins et al 2005), both cyclonic vortices and cyclonic-anticyclonic vortex couplets were observed. The cyclonic-only vortices were observed to form at all stages of bow echo evolution.…”
Section: Review Of Qlcs Circulationsmentioning
confidence: 95%
“…Based on numerical simulations, Weisman and Trapp (2003) and Trapp and Weisman (2003) propose that mesoy-scale vortices, or mesovortices within the bow echo are responsible for these narrow areas of damage. Several radar-based studies have confirmed the existence of damage-producing mesovortices in QLCSs (e.g., Atkins et al 2005;Wakimoto et al 2006a;Wheatley et al 2006). Trapp and Weisman (2003) suggest that vorticity couplets form within bow echoes (preferentially north of the bow apex) when baroclinically generated vorticity at the leading edge of the cold pool is tilted downward by subsystem-scale downdrafts and subsequently stretched, increasing the resulting vertical vorticity magnitude.…”
Section: Review Of Qlcs Circulationsmentioning
confidence: 96%
See 2 more Smart Citations